PERSEPSI SISWA TERHADAP TUTURAN IMPERATIF GURU DALAM INTERAKSI BELAJAR MENGAJAR BAHASA INDONESIA DI SMP NEGERI 3 SUNGGUMINASA - Harnum, Ade; Anshari; Usman (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research is a quantitative descriptive study that aims to describe students' perceptions of teacher imperative speech in teaching and learning interactions in Indonesian at SMP Negeri 3 Sungguminasa. The method used in this study is a survey method with data collection techniques using questionnaires. The population in this study was all class VIII students of SMP Negeri 3 Sungguminasa as many as 331 students, while the sample was 60 students. The research data was obtained by distributing questionnaires in hardcopy form to students. The results of the accumulation state that the indicator of attention is on the